The effect of demographic change on financial stability / Asma' Rashidah Idris, Muzafar Shah Habibullah and Shivee Ranjanee Kaliappan - Idris, Asma' Rashidah; Habibullah, Muzafar Shah; Kaliappan, Shivee Ranjanee (Universiti Teknologi MARA, Perlis, 2019)
This study investigates the effect of fertility on financial stability and its determinant particularly the relevance of demographic changes. This is motivated by the huge impact of demographic changes (increasing ageing population and low fertility level). Population ageing and low fertility tend to lower both labour- force participation and saving rates (change bank business model), thereby raising concerns on a future slowing economic growth and financial instability. The system GMM results show that the fertility level somehow acts as a buffer and reflects to the degree of stability to the financial system. An increase in fertility and old-age population will contribute to lowering the financial stability. As a matter of policy implication, the nations, financial sectors, and economies should take pro-active active steps and enhance policies in handling the inter-related issue of the ageing population, decreasing fertility, and financial stability especially in developed countries, but not necessarily to overlook the impact of the issues in developing countries.